Cyber-knife radiosurgery for spine and spinal cord tumors treatment - Pedachenko, Yu. E. (Ukrainian Neurosurgical Journal, 2009)
Radiosurgery is a new direction in treatment of different diseases, mainly oncology. After Gamma-knife clinical introduction the search of possibilities for radiosurgical interventions, performing in extracranial areas, including spine and spinal cord, has began. Basic principles of Cyber-knife-radiosurgery in treatment of spine and spinal cord tumors are described. Also an analysis of literature data was made, where results of 971 patients with spinal tumors using Cyber-knife were described. Taking into consideration novelty of this method (FDA permitted to use Cyber-knife in clinic only in 2001) sufficient follow-up information is absent, but first results are hopeful. Decrease of pain intensity was marked at 84–96% of patients with spinal tumors, local depression of tumor growth — at 75–100% (depending on tumor histological type). Complications and failures of Cyber-knife radiosurgery are conditioned by continuing tumor growth, neurological and common postradiation disorders. This review shows that Cyber-knife-radiosurgery is a perspective method for spinal and spinal cord tumors treatment.